(untitled) (Journal of the College of Basic Education, 2025)
The agricultural sector, both animal and plantation, has a prominent place in the Iraqi national economy. Buffalo farms are of great importance through their contribution to dairy products, as buffalo are raised primarily for milk production and contribute about 20% of the total milk production in Iraq, despite the small number of buffalo in Iraq. However, Iraqi buffalo milk receives great attention from citizens and occupies a special place in the Iraqi economic structure at the level of production, consumption and marketing. Therefore, Iraqi buffalo is one of the animals most closely associated with the aquatic environment due to the buffalo’s body’s need for water due to the high percentage of fat in buffalo milk, especially the buffalo of the marshes of southern Iraq and the Fadhiliya region in Baghdad Governorate. The aim of this research is to shed light on the problems facing buffalo breeders in Al-Fadhiliyah area in Baghdad Governorate. The analytical approach was adopted to analyze the information obtained through interviews conducted with the area’s residents who are specialized and experienced and direct questions to obtain the answer that can support the research with new information. It was found through the field visits conducted by the researcher that buffalo breeders in Al-Fadhiliyah area in Baghdad suffer from many problems in raising buffalo that should be highlighted. One of the most important problems facing buffalo breeders is the distance of water sources from the buffalo breeding pens. As it is known, Al-Fadhiliyah area is located close to the Diyala river, so buffalo breeders suffer from taking buffalo from the buffalo pens to the banks of the Diyala River, as water is one of the most important sources of buffalo breeding, especially in the summer.